Farmers knowledge on input usage and its effect on environment - Shubashree, V; Vinayagam, S Senthil; Akhila, K (Indian Farming, 2024)
Agriculture sector plays key role in enhancement of economic growth and environmental sustainability. Paddy, maize, cotton, tobacco were major crops grown in India. Maize and Tobacco were the third most important commercial food crop and commercial crop in the world respectively. Paddy is the only source of income for majority of people in our country. India is one of the largest producers as well as exporters of cotton yarn. The efficient usage of inputs aids to facilitate optimum growth and maximum yield. Now-a-days the farmers should be aware regarding usage of inputs specifically water requirement, nutrient uptake, pesticide usage etc. The present study reveals the farmers knowledge on water requirement which includes cost of irrigation service, economic factors, education and technical factor, social factor, legal and institutional factor. It also revealed that tobacco farmers who contributed 52% of the total farmers surveyed have taken up soil test with the support of crop institutions, corporates and thereby following soil test-based fertilizer recommendation for tobacco and one third of the farmer’s had knowledge about the pesticide usage was due to the marketing activities of the companies. Most of the farmers were having personal protective equipment’s. The major challenges include runoff of fertilizes and adding up to water table, eutrophication, algal blooms, harm to human and animal health on use of pesticides.